2019
DOI: 10.1016/j.jesp.2019.103836
|View full text |Cite
|
Sign up to set email alerts
|

Group identities benefit well-being by satisfying needs

Abstract: Although research has highlighted the importance of differentiating between different types of social ties-group ties and individual ties-no experimental work exists that investigates the claim that group ties are more beneficial than individual ties, and little is known about how group memberships influence well-being, relative to relationships. We designed a series of experiments that: a) primed either multiple group memberships or multiple interpersonal relationships (vs. films) and observed the effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 79 publications
2
22
0
Order By: Relevance
“…Seeking to explain why social relations and groups might be beneficial for prisoners, we also provide the first evidence that a fulfilling social life in prison fosters the psychological needs of connectedness (social support and relatedness), self-worth (self-esteem and competence), and volitional agency (autonomy, control, and meaning). Our mediation findings complement and extend previous work that has found that these psychological needs can account for social cure effects in non-offender populations (Kyprianides, Easterbrook, & Brown, 2019: connectedness and self-worth; Koudenburg et al, 2017: autonomy;Greenaway et al, 2016: control and meaning), and provide a novel explanation of the beneficial effects of social relations and groups on prisoner well-being. It is worth noting that the capability of prisoner relations and prisoner groups to fulfil the need of autonomy was demonstrated in both Studies 1 and 2.…”
Section: Individual and Group Ties Satisfy Psychological Needssupporting
confidence: 87%
See 1 more Smart Citation
“…Seeking to explain why social relations and groups might be beneficial for prisoners, we also provide the first evidence that a fulfilling social life in prison fosters the psychological needs of connectedness (social support and relatedness), self-worth (self-esteem and competence), and volitional agency (autonomy, control, and meaning). Our mediation findings complement and extend previous work that has found that these psychological needs can account for social cure effects in non-offender populations (Kyprianides, Easterbrook, & Brown, 2019: connectedness and self-worth; Koudenburg et al, 2017: autonomy;Greenaway et al, 2016: control and meaning), and provide a novel explanation of the beneficial effects of social relations and groups on prisoner well-being. It is worth noting that the capability of prisoner relations and prisoner groups to fulfil the need of autonomy was demonstrated in both Studies 1 and 2.…”
Section: Individual and Group Ties Satisfy Psychological Needssupporting
confidence: 87%
“…Greenaway et al, 2016). A particularly relevant study by Kyprianides, Easterbrook, and Brown (2019) demonstrated that the beneficial consequences of thinking about social groups when feeling down, and the ability of groups to promote a positive outlook on life, was partly due to the greater feelings of connectedness to others (operationalised as feelings of support and relatedness) and sense of self-worth (operationalised as feelings of self-esteem and competence) that groups provide.…”
Section: Psychological Resources As a Mediatormentioning
confidence: 99%
“…Quite why group memberships can have curative properties is not yet well understood, although it seems likely that they provide people with a sense of belonging, feelings of efficacy and social support (Greenaway, Cruwys, Haslam & Jetten, 2015;Kyprianides, Easterbrook & Brown, 2019). What is interesting, though, is that, notwithstanding the intellectual debt that social cure research owes to SIT, the only aspect in SIT itself that predicted well-being benefits of groups was its core hypothesis that the 'search for distinctiveness' was motivated by a need for positive self-esteem among group members; presumably, if distinctiveness was achieved, people's well-being would increase.…”
mentioning
confidence: 99%
“…These varied types of groups can be difficult to differentiate from their component social relationships (and social roles). Some researchers have attempted to distinguish independent associations of social relationships and social group memberships with health and well-being, sometimes arguing that social identities are even more influential than social relationships (e.g., Kyprianides et al, 2019;Sani et al, 2012). Other work in this tradition has asserted that sheer quantity of social group memberships alone is predictive of health outcomes, with "the more the merrier" (e.g., Jetten et al, 2015;Jones & Jetten, 2011).…”
Section: Social Groupsmentioning
confidence: 99%